The Use of Nurse Checklists in a Bedside Computer-Based Information System to Focus on Avoiding Secondary Insults in Neurointensive Care. (15th July 2012) - Nyholm, Lena; Lewén, Anders; Fröjd, Camilla; Howells, Tim; Nilsson, Pelle; Enblad, Per
Abstract : The feasibility and accuracy of using checklists after every working shift in a bedside computer-based information system for documentation of secondary insults in the neurointensive care unit were evaluated. The ultimate goal was to get maximal attention to avoid secondary insults. Feasibility was investigated by assessing if the checklists were filled in as prescribed. Accuracy was evaluated by comparing the checklists with recorded minute-by-minute monitoring data for intracranial pressure-ICP, cerebral perfusion pressure CPP, systolic blood pressure SBP, and temperature. The total number of checklist assessments was 2, 184. In 85% of the shifts, the checklists were filled in. There was significantly longer duration of monitoring time at insult level when Yes was filled in regarding ICP (mean 134 versus 30 min), CPP (mean 125 versus 26 min) and temperature (mean 315 versus 120 min). When a secondary insult was defined as >5% of monitoring time spent at insult level, the sensitivity/specificity for the checklist assessments was 31%/100% for ICP, 38%/99% for CPP, and 66%/88% for temperature. Checklists were feasible and appeared relatively accurate. Checklists may elevate the alertness for avoiding secondary insults and help in the evaluation of the patients. This concept may be the next step towards tomorrow critical care.